Dualisme Konsep Yom YHWH dalam Pengharapan Mesianik Nabi Zefanya - Gernaida Krisna R. Pakpahan (THRONOS: Jurnal Teologi Kristen, 2022)
This article seeks to highlight the problem of the theological complexity of the prophet Zephaniah regarding the idea of yom YHWH, or "the day of the Lord," which contrasts divine judgment with the joy of messianic restoration. The Prophet's oracle quickly turns into two conflicting nodes that show the richness and dynamics of the Prophet's thought. The primary purpose of this analysis is to explore the dual nature of the Lord's day in the book of Zephaniah. Through the historical approach of dualism, the idea of yom YHWH has been expressed in 1) Dimensions of YHWH's judgment: Judah and the nations; 2) YHWH's judgment time: very near and far in the future; 3) The promise of salvation to Judah and the nations; 4) YHWH's judgment in the destruction and restoration of nature; 5) The universal messianic hope. AbstrakArtikel ini berusaha untuk menyoroti masalah kompleksitas teologi dari nabi Zefanya tentang gagasan yom YHWH  atau “hari Tuhan” yang mengontraskan penghakiman ilahi dengan sukacita pemulihan mesianis. Orakel nabi cepat berubah dalam dua titik simpul yang saling bertentangan  yang memperlihatkan kekayaan dan dinamika pemikiran nabi. Tujuan utama dari analisis ini adalah menggali dualisme sifat hari Tuhan yang dalam kitab Zefanya. Melalui pendekatan historis dualisme gagasan yom YHWH dinyatakan dalam: 1) Dimensi penghukuman YHWH: Yehuda dan bangsa-bangsa;  2) Waktu penghakiman YHWH:  sangat dekat dan jauh di masa depan; 3) Janji keselamatan bagi Yehuda dan bangsa-bangsa; 4) Penghakiman YHWH dalam kehancuran dan pemulihan alam; 5) Pengharapan mesianik universal.